1959
DOI: 10.1126/science.129.3354.967
|View full text |Cite
|
Sign up to set email alerts
|

Role of Myocardial Catecholamines in Cardiac Contractility

Abstract: In cats bilateral sympathectomy or administration of reserpine results in a marked reduction in concentration of myocardial catecholamines. The contractility of papillary muscles from such animals is significantly less than that of muscles from untreated animals. These findings demonstrate the importance of normal levels of myocardial catecholamines in the maintenance of normal cardiac contractility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1

Year Published

1960
1960
1989
1989

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 3 publications
3
23
1
Order By: Relevance
“…A decrease in the sympathetic support to the myocardium might be expected to compromise the heart's performance further. Indeed, some (35), although not all, experiments have suggested that when cardiac norepinephrine stores are reduced, either by reserpine or surgical sympathectomy, to levels comparable to those observed in congestive heart failure, a decline in the contractile state of the heart muscle occurs. A more complete understanding of the mechanisms responsible for the biochemical abnormality described in this report may provide an additional approach to the clinical management of congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the sympathetic support to the myocardium might be expected to compromise the heart's performance further. Indeed, some (35), although not all, experiments have suggested that when cardiac norepinephrine stores are reduced, either by reserpine or surgical sympathectomy, to levels comparable to those observed in congestive heart failure, a decline in the contractile state of the heart muscle occurs. A more complete understanding of the mechanisms responsible for the biochemical abnormality described in this report may provide an additional approach to the clinical management of congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…The action potential abolished by the a-receptor blocking agents were restarted by ACh (2,3). Several investigators (7)(8)(9)(10) assumed that the stimulating effect of ACh related with endogenously liberated catecholamine. However, the addition of ACh restarted the action potential arrested by the a-receptor blocking agents even in the reserpinized rabbit, as described in the previous report (2).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, experiments on the atrial preparation under depletion of the cate cholamines might provide a clue to know whether they are concerned with initiation and maintenance of the atrial activity. Since reserpine above the dose of 1.0 mg/kg depletes more than 90% of the normal content of the catecholamines in the heart of cat (17), dog (18,19), rabbit (13,20) and rat (21), and moreover the depletion of catecholamines from the extirpated organ occurs following in vitro administration of reserpine, the effects of reserpine on the action potential of isolated atrial fibers were studied when it was applied into the atrial chamber.…”
Section: Discussionmentioning
confidence: 99%